2006
DOI: 10.1002/ajim.20334
|View full text |Cite
|
Sign up to set email alerts
|

Diachronic study of pleural plaques in rural population with environmental exposure to asbestos

Abstract: Radiological appearance of pleural plaques and respiratory function of people previously exposed to asbestos environmental pollution worsens over the years. Prevalence of mesothelioma was found to be higher than expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Cookson described the progression as continuous after the disease is established [Cookson et al, 1986]. A paper by Sichletidis et al [2006] demonstrated slow progression of plaques with attendant loss of lung function in a series of environmentally exposed cases in Greece. A recent article by Larson [Larson et al, 2010] describes the progression of plaques and other changes using sequential chest X-rays obtained between 1955 and 2004 among Libby vermiculite workers.…”
Section: Discussionmentioning
confidence: 99%
“…Cookson described the progression as continuous after the disease is established [Cookson et al, 1986]. A paper by Sichletidis et al [2006] demonstrated slow progression of plaques with attendant loss of lung function in a series of environmentally exposed cases in Greece. A recent article by Larson [Larson et al, 2010] describes the progression of plaques and other changes using sequential chest X-rays obtained between 1955 and 2004 among Libby vermiculite workers.…”
Section: Discussionmentioning
confidence: 99%
“…There are no data on the risk of lung cancer due to childhood exposures. Increased lung cancers have been observed in inhabitants of villages situated near natural outcrops of asbestos in both China [Luo et al, 2003] and Greece [Sichletidis et al, 2006] but, unlike the Wittenoom cohort, the villagers in these studies had had a lifetime of exposure. Other studies have not found an association between environmental exposures to asbestos and lung cancer [Hammond et al, 1979; Camus et al, 1998; Magnani and Leporati, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Kopylev et al 1 cited a longitudinal study3 showing lung function decrements over time in a population with pleural plaques. As this study had no comparison population, it is impossible to determine the cause of lung function loss.…”
mentioning
confidence: 99%